2012
DOI: 10.1136/jnnp-2012-302273
|View full text |Cite
|
Sign up to set email alerts
|

Clonazepam Quiets tinnitus: a randomised crossover study withGinkgo Biloba

Abstract: Clonazepam is effective in treating tinnitus; G biloba is ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…Clonazapam has shown improvement in tinnitus in one study 41 , while another study suggests clonazepam is only effective when used in combination with Deanxit 42 . In contrast, one clinical trial determined no efficacy with Bartels 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Clonazapam has shown improvement in tinnitus in one study 41 , while another study suggests clonazepam is only effective when used in combination with Deanxit 42 . In contrast, one clinical trial determined no efficacy with Bartels 43 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in some studies and clinical trials it has been stated that this herb has no beneficial effect in comparison with placebo in the treatment of tinnitus (Table 2). There are many studies on the effects of Ginkgo biloba in the treatment of patients with tinnitus that most of the findings of these studies are in contrast with each other; on the one hand, some of the studies reported that Ginkgo biloba is effective in the treatment of tinnitus effective [48][49][50][51][52][53] and on the other hand other studies referred to it as ineffective herbal medicine 28,[54][55][56][57] . The results of a systematic review showed that Ginkgo biloba is little/less effective in the treatment of tinnitus.…”
Section: Resultsmentioning
confidence: 61%
“…Han and colleagues30 report a cross-over trial of clonazepam and ginko biloba for the treatment of tinnitus (see page ) . In this methodically and analytically strong report, the authors used comprehensive psychophysical techniques to objectively assess the severity of tinnitus and used such quantitative outcome measures to prove the efficacy of clonazepam for the treatment of tinnitus.…”
Section: Increased Spontaneous Activity and Pharmacotherapy Of Tinnitmentioning
confidence: 99%